Ex-Officio Rights of the Judges in Signating the Holder of Currency: Hadhanah in Directions of Divorce at the Religious Court as an Efforts of Legal Protection and Administration of Legal Certainity for Children - Muhammad Fadhly Ase (International Journal of Nusantara Islam, 2019)
Child custody (hadhanah) is a problem that often occurs in divorce. This is because divorce often still leaves problems. Divorce only breaks the legal relationship between husband and wife and changes the status of each to a former husband and ex-wife but does not reduce conflicts between them. The conflict between the parents which then leads to a struggle for custody of the child clearly greatly affects the psychological condition of the child. It is the duty of a judge to provide the best interests as a form of protection for the child. The results of this study indicate: the right of ex officio judges is used or applied in the context of certainty, justice and legal benefits for both parties and especially for the child himself, hadhanah or post-divorce care for the child places the child's position as a party that must be protected and is a joint obligation of both parents. in the best interest of the child.